Total systems design of Icannhas, Inc. - Boydon, Christian John Immanuel S.; Santos, Abbi D.; Torre, Alyssa Jessica P.; Villanueva, Rose Ann S.
Icannhas, Inc. is a software development and design company that specializes in the creation of various mobile and online applications, design and development of websites, as well as the development of quality software solutions for various clients, both local and international. It is a start-up company has only been in operation for three years and currently employs 36 employees. The company employs an informal, family-like work culture that allows its employees to work in a flexitime and flexiplace setting. This type of setting is conducive to the relaxation and creativity of the company's employees, who are considered as the company's greatest asset, which allows them to come up with innovative and quality solutions that will satisfy the company's clients. This work culture however may become damaging to the company if handled irresponsibly, such as increasing the frequency of firing employees because of their inability to keep up with the said culture. This issue is currently being experienced by Icannhas, Inc. lowering its employee retention rate to 62% which is significantly lower compared to the average employee retention rate of companies in the IT industry which is at 78%. This low retention rate leads to poor knowledge turnover in the company as well as delays in project completions and decrease in profit margins. The analysis of employee data shows that the majority of the employees who left the company left within their first six months of employment in the company mainly because of their incapability of handling the workload and maturity demanded by their work, resulting to poor outputs and delays in project completion. This suggests that either the current screening process of the company is ineffective or that its training method is lacking. In order to address this, modifications in the company's currently horizontal and flat structure was advised. The modification of a company's organizational structure would greatly affect its culture and therefore the results that it would produce. In order to achieve the desired increase in employee retention, while maintaining the good quality of output being produced by the company as well as not limiting the current benefits being employed by the employees, the modifications proposed in this paper mainly focused on the recruitment and training aspects of the company. Such modifications include the addition of a Human Resources Committee as well as a Training committee. Other proposed modifications in the company's structure include the formation of a Finance Committee as well as a Marketing and Project Process Committee. These additional committees redistributes the functions of the CEO to senior and mature employees of the company for better knowledge turnover and documentation in the company. The proposed changes in the system aims to ensure business continuity with minimal effects on the freedom and perks currently being enjoyed by the company's employees.